Express train-quality monitoring of the condensed materials heat conductivity; 12th International conference on methods of aerophysical research (ICMAR 2004), 28 June - 4 July 2004, Akademgorodok, Novosibirsk, Russia; Рart 3 - Shilyaev A. M. (2004, 2004)
В фонде НТБ ТПУ отсутствует